2002
DOI: 10.1074/jbc.m202517200
|View full text |Cite
|
Sign up to set email alerts
|

Physical Interaction between Recombinational Proteins Rhp51 and Rad22 in Schizosaccharomyces pombe

Abstract: In eukaryotes, Rad51 and Rad52 are two key components of homologous recombination and recombinational repair. These two proteins interact with each other. Here we investigated the role of interaction between Rhp51 and Rad22, the fission yeast homologs of Rad51 and Rad52, respectively, on the function of each protein. We identified a direct association between the two proteins and their self-interactions both in vivo and in vitro. We also determined the binding domains of each protein that mediate these interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…However, since the RPA levels in the unbound fractions increased only slightly when Rad22 was also included (Figure 4H), the observed increase of Rhp51 in Figure 4I may be due to Rhp51 bound to RPA-coated css beads via Rad22. It has been reported that Rad22 interacts with both Rhp51 and RPA [31,32], and the ternary complex can also be detected in vitro by coimmunoprecipitation (unpublished data). However, RPA displacement mediated by Rhp51 with Swi5-Sfr1 was further stimulated by coincubation with Rad22 (Figure 4G).…”
Section: Resultsmentioning
confidence: 92%
“…However, since the RPA levels in the unbound fractions increased only slightly when Rad22 was also included (Figure 4H), the observed increase of Rhp51 in Figure 4I may be due to Rhp51 bound to RPA-coated css beads via Rad22. It has been reported that Rad22 interacts with both Rhp51 and RPA [31,32], and the ternary complex can also be detected in vitro by coimmunoprecipitation (unpublished data). However, RPA displacement mediated by Rhp51 with Swi5-Sfr1 was further stimulated by coincubation with Rad22 (Figure 4G).…”
Section: Resultsmentioning
confidence: 92%
“…The N-terminal ends of Rad52 homologs are required for self-interaction, DNA binding, and annealing and thus play a key role in the function of these proteins (Asleson et al 1999). The C-terminal regions are required for interaction with Rad51 and are more species specific (Milne and Weaver 1993;Kagawa et al 2002;W. J. Kim et al 2002) (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Rad22 is the fission yeast homologue to budding yeast Rad52, which is responsible for loading Rhp51 onto 3Ј end of ssDNA (Kim et al, 2002). Some recombination events in fission yeast such as single-strand annealing are Rad22 de- pendent but Rhp51 independent .…”
Section: Recombinases Are Not Required For Replication Slowingmentioning
confidence: 99%